Exploration of Geometry Concepts in the Tafatik Maromak Oan Malaka Traditional House - Tahu, Oktaviani Marisa; Son, Aloisius Loka; Deda, Yohanes Ndapa (S&Co Publishing, 2023)
Ethnomatematics is an intersection between mathematics and culture, making it a study of mathematical concepts within a specific cultural context. In line with this, the present research aimed to explore the mathematical concepts present in the Tafatik Maromak Oan traditional house. This research is qualitative research with an ethnographic approach. This research was conducted in August 2022 in Wehali Village, Central Malaka District, Malaka Regency. The instruments used are observation guidelines, interview guidelines, and documentation. Participants in this study consisted of 4 people with details of 1 King (Nain), 1 traditional housekeeper (fukun), 1 craftsman and 1 community member. The stages in this study consisted of domain analysis, taxation analysis, componential analysis, analysis of cultural themes, and drawing conclusions. The results of this study indicate that the mathematical concepts contained in the Tafatik Maromak Oan Malaka traditional house are geometric concepts including rectangles, squares, triangles, circles, lines, cylinders and trapezoids.